Density Functional Based Tight Binding Study on Wurzite ZnS Nanowires - Lien, Le Thi Hong; Tuoc, Vu Ngoc; Thuong, Nguyen Thi (Communications in Physics, 2013)
We present a semi-abinitio - Density Functional Based Tight Binding (DFTB) study on the atomic and electronic structure of ZnS Nanowire (NW) and examine the dependence of surface stress on nanowire lateral size and shape. The ZnS wurtzite wire size ranges from 10 to 45Å and of various possible shapes - triangular, hexagonal and circular-like. We investigate the role of unsaturated dangling bond state in the region of band gap varying the wire's diameter. We have calculated the surface formation energy and find that it decreases with increasing the wire diameter and a greater stability (lower surface formation energy) comes with hexagonal and circular-like depending on wire's diameter. Other electronics and mechanical properties e.g. density of states (DOS), Young modulus...  also are found to depend on the wire's size and shape. Futher the wire passivation by hydrogen has also investigated.